Electrochemical Activity of Cytochrome P450 1A2: The Relevance of O2 Control and the Natural Electron Donor. Issue 3 (18th December 2020) - Silveira, Célia M.; Rodrigues, Patrícia R.; Ghach, Wissam; Pereira, Sofia A.; Esteves, Francisco; Kranendonk, Michel; Etienne, Mathieu; Almeida, M. Gabriela
Abstract: The direct electrochemical response of membrane‐bound human cytochrome P450 1A2 (CYP1A2) was studied on pyrolytic graphite electrodes, while encapsulated in a sol‐gel matrix. The enzymatic reduction of O2 was evaluated in the presence and absence of its electron donor partner, cytochrome P450 oxidoreductase (CPR). When used without CPR, CYP1A2 was shown to be highly sensitive to O2 even in the presence of residual amounts. Under aerobic conditions (air‐saturated solutions), the catalytic signal attributed to the reaction with O2 was lost, suggesting the enzyme was inactivated. In contrast, the CYP1A2/CPR complex retained O2 reductase activity with high O2 concentration in solution. The results demonstrated a crucial role of CPR in stabilizing the immobilized CYP1A2 enzyme and in the preservation of O2 electrocatalysis, when using this electrochemical set‐up. Though the enzyme's monooxygenase activity towards caffeine was not detected, this study highlights the complexity of coupling CYP1A2 reduction currents with substrate turnover, owing to the simultaneous electrochemical measurement of the O2 reduction reaction. Abstract : In control : Cytochrome P450 1A2 (CYP1A2) direct electrochemistry is obtained on a biocompatible sol‐gel film. Control of O2 levels is critical to get reliable results on the enzyme's activity. The electrocatalytic activity towards O2 depends on interaction with the electron donor CYP oxidoreductase (CPR).